2015
DOI: 10.3390/molecules201018144
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity, Antioxidant Effect and Chemical Composition of Propolis from the Región del Maule, Central Chile

Abstract: Propolis is commercialized in Chile as an antimicrobial agent. It is obtained mainly from central and southern Chile, but is used for the same purposes regardless of its origin. To compare the antimicrobial effect, the total phenolic (TP), the total flavonoid (TF) content and the phenolic composition, 19 samples were collected in the main production centers in the Región del Maule, Chile. Samples were extracted with MeOH and assessed for antimicrobial activity against Gram (+) and Gram (−) bacteria. TP and TF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 46 publications
3
53
1
5
Order By: Relevance
“…Samples 17 and 18 showed considerable activity against c. albicans. Antifungal effects have been described previously (Kujumgiev et al 1999;Moreno et al 1999;Sawaya et al 2002), although studies have also shown that propolis may have no anti-candidiasis effect (Nina et al 2015). In our study, there were large differences in anti-candidiasis efficacy, indicating differences in origin as a source of variability in the sample activity, an idea which is further supported by the observation that samples from the same region had similar antifungal properties.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Samples 17 and 18 showed considerable activity against c. albicans. Antifungal effects have been described previously (Kujumgiev et al 1999;Moreno et al 1999;Sawaya et al 2002), although studies have also shown that propolis may have no anti-candidiasis effect (Nina et al 2015). In our study, there were large differences in anti-candidiasis efficacy, indicating differences in origin as a source of variability in the sample activity, an idea which is further supported by the observation that samples from the same region had similar antifungal properties.…”
Section: Discussionsupporting
confidence: 86%
“…The results are presented as MIC values (Table 1), except for e. coli since no antibacterial activity could be detected and all MIC values were above 50 mg/ml. Nina et al (2015) described limited activity of propolis samples from Argentina against e. coli, while others (Boyanova et al 2006;Kosalec et al 2007) found no inhibitory activity of Bulgarian and Brazilian propolis, respectively, against e. coli. Kosalec et al (2007) found MIC values of below 10.4 mg/ml against e. coli while testing Croatian propolis samples.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis from Chile has been reported to contain nine flavones/flavonol derivatives, one flavanone, eight dihydroflavonols and nine phenyl-propanoids [43]. Cinnamic acid derivatives and flavonoids are capable of affecting bacterial membrane potential by interfering with ion permeability leading to inhibition of bacterial mobility [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is extensively used for centuries, in foodstuffs and beverages to improve health related disorders. Propolis and geopropolis exhibited a wide variety of pharmacological properties, such as, anti-inflammatory, antioxidant, antitumor, antiulcer and for treatment of respiratory diseases (Berretta et al, 2017;Montenegro & Mejí as, 2013;Pippi et al, 2015;Nina et al, 2015). The antiviral activity of propolis from different geographic regions is known, since ancient times.…”
Section: Introductionmentioning
confidence: 99%